Browse use and small ruminant production in Southeast Nigeria. Proceedings of a symposium - Reynolds, L.; Atta-Krah, A.N. (International Livestock Centre for Africa, 1987)
Presents papers that discusses results of research conducted so far on browse use and small ruminant production in southeast Nigeria. Examines sheep and goat production in humid Cross River state. Presents results of surveys on small ruminant population and farming systems in Cross Rivers State; browse plants in upland areas of rivers state; and local browse species used by sheep & goats and management system in Imo state. Discusses the establishment and evaluation of local browse species alongside Leucaena & Gliricidia; and establishment, growth and performance of browse species in Southeast Nigeria. Also presents results of Gliricidia and Leucaena germplasm evaluation trials